Biological activity of folkloric plants used in the treatment of 'u wela' against pathogens - Tryphina T. Ramavhale; Salome M. Mahlo; Jacobus N. Eloff (AOSIS, 2024)
Background: 'U wela' also known as 'Divhu' in 'Tshivenda' is a sexually transmitted infection caused by a combination of fungal and bacterial microorganisms that affects males because of unprotected sexual encounters with a woman who has had an abortion or miscarriage. Aim: The study aimed to investigate medicinal plants used to treat 'u wela' and determine their biological activity against Neisseria gonorrhoeae and Candida albicans. Setting: Eight plant species (Elaeodendron transvaalense[Burtt Davy] R.H. Archer, Albizia versicolor Welw. ex Oliv, Xanthocercis zambesiaca Baker, Cassia abbreviata subsp. beareana [Holmes] Brenan, Anthocleista grandiflora Gilg, Myrothamnus flabellifolius Welw., Mimusops zeyheri Sond, and Capparis tomentosa Lam.) used to combat 'u wela' were selected from the Ethnomedicinal plant's database of over 300 medicinal plants used for medicinal purposes in humans, in the Vhembe district, Limpopo province, South Africa. Methods: The antimicrobial activity of the plant extracts was investigated against Candida albicans and Neisseria gonorrhoeae using serial dilution and bioautography assays. Results: The plant extracts of A. versicolor and C. abbreviata had excellent activity with a low minimum inhibitory concentration (MIC). value of 0.02 and 0.07 mg/mL, respectively. In bioautograms developed in benzene/ethanol/ammonia hydroxide (BEA), active compounds were visible in the extracts of A. versicolor. Conclusion: A. versicolor had excellent antimicrobial activity and may be used in traditional therapy to combat 'u wela'. Contribution: The study has demonstrated that A. versicolor is a promising plant species that could lead to the discovery of novel drugs to combat 'u wela'.